Hubungan Partisipasi Ekstrakurikuler Cricket dengan Tingkat Kebugaran Jasmani Siswa SDN Petukangan Utara 07 Pagi, Jakarta Selatan - Hilma Nadiya; Ajo Sutarjo; Tomi Efendi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to assess the physical fitness level of students participating in cricket extracurricular activities and to analyze the relationship between participation level and physical fitness at SDN Petukangan Utara 07 Pagi, South Jakarta. The research employed a quantitative approach with a correlational design. The sample consisted of 30 students from grades III to VI, selected based on their attendance during data collection. The research instruments included a participation questionnaire consisting of 20 Likert-scale items and the Indonesian Student Fitness Test (Tes Kebugaran Pelajar Nusantara / TKPN), which measures Body Mass Index (BMI), V Sit and Reach, Sit-Up, Squat Thrust, and Progressive Aerobic Cardiovascular Endurance Run (PACER). Data were analyzed descriptively and inferentially using Pearson correlation test with SPSS version 25 after meeting normality and linearity assumptions. The results showed that the average TKPN score was 2.91, categorized as moderate. The correlation test yielded r = 0.859 with p < 0.05, indicating a very strong and significant relationship between cricket extracurricular participation and students' physical fitness. In conclusion, participation in cricket extracurricular activities contributes 73.8% to the physical fitness of elementary school students. Keywords: Cricket Extracurricular, Elementary School, Physical Fitness